Peran Bidan Dalam Menghadapi Budaya Panggang Dan Tatobi Ibu Nifas Pada Suku Timor Di Kecamatan Mollo Tengah Kabupaten Timor Tengah Selatan Tahun 2016 - Astin Nur Hanifah (JURNAL INFO KESEHATAN, 2018)
Background: The culture of the Timorese people in South Central Timor Regency is that mothers are required to give birth at a roundhouse and receive treatment for 40 days by a shaman or someone who is believed to have experience in caring for the mother. Treatment for postpartum mothers is usually in the form of roasting fire and hobbies. This fact will have a bad effect on the mother and baby will burn his body and affect wound healing after childbirth. In addition, due to the lack of a clean home environment because all the activities for maintenance are carried out inside the house, such as cooking and roasting so that the mother and baby are having an ARD. The risk of grilling/sei and tatobi is ARI, anemia, burns and dehydration and burns and fires can occur. Bake is also very risky for the onset of anemia in postpartum mothers due to a large amount of blood coming out of the birth canal due to continuous roasting and blood vessel dilation that causes a lot of bleeding and is difficult to control. Objective: identify the role of midwives in the community in dealing with the culture of roasting and hobbies for Timorese postpartum women in South Central Timor Regency in 2016. Research Methods: a type of descriptive research with a qualitative approach. Research Results: The mother of the Mollo Tengah village community still adheres to the tradition of grilling and tatobi. Baked them do in a roundhouse, trusted by the local community for antidotes to severe pain especially in women after childbirth. Another reason for grilling fire or a hobby is the concern of parents if the child's body condition becomes weak and not strong. Some postpartum mothers experience anemia, babies experience ARI and sunburn. Has an effect on wound healing after childbirth. Basically, midwives have carried out the main duties of midwives in the community as an implementer, manager, and educator. Conclusions: the activities that have been carried out by midwives in the Mollo Tengah sub-district health center are home visits, counseling conducted on maternal and child health targets, and doing cadre refreshing, including asking for help from health cadres and traditional healers to disseminate information about safe roasts by paying attention to the distance between the coals and the mother's bed, and the hobbies using only warm water. In addition, health cadres were also invited to do mapping of targeted data for mothers and children (pregnant women, postpartum mothers, infants, and toddlers) in the community. Activating tabulin and waiting for homes so that the waiting house can function properly.